IL-10 Indirectly Downregulates IL-4–Induced IgE Production by Human B Cells - Lin, Adora A; Freeman, Alexandra F; Nutman, Thomas B (ImmunoHorizons, 2018)
Controlled allergic disease is associated with decreased allergen-specific IgE and increased allergen-specific IgG4. Although IL-10 has been shown to contribute to these changes, the underlying mechanisms are largely unknown. This study explored how IL-10 differentially regulates human IgE and IgG4 production. Highly purified B cells and B cell subsets from healthy individuals were cultured with combinations of anti-CD40, IL-4, and IL-10. In other experiments, PBMCs isolated from healthy donors or from autosomal dominant hyper-IgE syndrome (STAT3 loss-of-function) subjects were cultured with combinations of IL-4 and IL-10. In B cell cultures, IL-10 had no significant effect on IL-4–induced IgE production but increased IL-4–induced IgG4 production over 20-fold. IL-4–induced transcription of Cε and Cγ4 germline transcripts (GLTs) by isolated B cells was not affected by IL-10. In PBMC cultures, IL-4 induced production of both IgE and IgG4 and increased expression of Cε and Cγ4 GLTs above baseline. Unlike in purified B cells, IL-10 diminished IL-4–induced IgE production and expression of Cε GLTs without affecting IgG4 production or expression of Cγ4 GLTs. PBMCs from autosomal dominant hyper-IgE syndrome individuals failed to consistently modulate IgE production in response to IL-4 and IL-10. As measured by flow cytometry, the frequency of IL-10R+ cells was similar between IgE+ and IgG4+ B cells. These data suggest that IL-10 acts indirectly through accessory cells to modulate the production of IgE. For IgG4, IL-10 appears to act directly on B cells to drive IgG4 production, with its effects being downstream of germline transcription.